Exploring the therapeutic potential of recombinant human lysozyme: a review on wound management system with antibacterial - Zhao, Meiping; Huang, Meili; Li, Zhen (Frontiers in Bioengineering and Biotechnology, 2023)
Lysozyme, a natural antibacterial enzyme protein, possesses the ability to dissolve the cell walls of Grampositive bacteria, demonstrating broad-spectrum antibacterial activity. Despite its significant potential in treating wound infections and promoting wound healing, its widespread clinical application has yet to be realized. Current research is primarily focused on carrier-based delivery systems for lysozyme. In this review, we discuss four delivery systems that can be employed for lysozyme in wound healing treatment, specifically hydrogels, nanofilms, electrospun fibrous membranes, and modified-lysozyme composite systems. These systems not only enhance the stability of lysozyme but also enable its controlled and sustained release at wound sites, potentially overcoming some of the challenges associated with its direct application. Lastly, we delve into the perspectives and challenges related to the use of these delivery systems, hoping to spur further research and innovation in this promising field.